2015
DOI: 10.1371/journal.pone.0135049
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Status: Impact of Short-Term Ischemia on Follicular Survival of Whole Ovarian Transplantation in a Rabbit Model

Abstract: Ischemia is the first mechanism that provokes the loss of follicles in ovarian grafts over the long term. In whole ovarian transplantation, it remains unknown, however, how changes in follicular development are influenced by short-term ischemia. Fresh whole ovarian orthotopic auto-transplantation was performed in rabbits with 45 min ischemia, and the impact of ischemia on follicular survival and development status was evaluated at different time-points (1 day, 3 days, 1 week, 2 weeks and 1 month). Assessment o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 39 publications
(43 reference statements)
2
7
0
Order By: Relevance
“…Simultaneously, during the same period, increase of the number and volume of tertiary follicles showed follicular growth continued and was enhanced after heterotopic transplantation. Consistent with our findings, Xie et al [ 3 ] recently showed that healthy rate of follicles and the number of follicles with positive proliferating cell nuclear antigen in primary follicles decreased 1 month after orthotopic autografting of the rabbit ovaries. Early follicular development is regulated by ovarian autocrine/paracrine regulators and interactions between oocyte-granulosa cells, ovarian stromal cells, and theca cells affect this process [ 14 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Simultaneously, during the same period, increase of the number and volume of tertiary follicles showed follicular growth continued and was enhanced after heterotopic transplantation. Consistent with our findings, Xie et al [ 3 ] recently showed that healthy rate of follicles and the number of follicles with positive proliferating cell nuclear antigen in primary follicles decreased 1 month after orthotopic autografting of the rabbit ovaries. Early follicular development is regulated by ovarian autocrine/paracrine regulators and interactions between oocyte-granulosa cells, ovarian stromal cells, and theca cells affect this process [ 14 ].…”
Section: Discussionsupporting
confidence: 93%
“…On the other hand, ovarian transplantation has the potential application for maintaining the fertility after chemotherapy and radiotherapy in women [ 2 ]. As a result of the ovarian transplantation, the possible depletion of follicle reserve and limitation of fertility restoration exist [ 3 ]. The major concern in grafting is that the graft survival is completely dependent on the establishment of neovascularization [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Vascular transplantation of fresh whole ovaries has been largely successful in animal models (rats [ 103 , 104 , 105 ], rabbits [ 106 , 107 , 108 , 109 , 110 , 111 , 112 , 113 , 114 ], sheep [ 47 , 49 , 67 , 68 , 78 , 115 , 116 , 117 , 118 , 119 , 120 , 121 ], pigs [ 122 , 123 ], dogs [ 124 ] and monkeys [ 125 , 126 ]). Encouraging results have also been reported on transplantation of frozen–thawed whole ovaries in rats [ 66 , 127 , 128 , 129 ], rabbits [ 130 ] and sheep [ 38 , 40 , 41 , 48 , 49 , 50 , 67 , 68 , 78 , 95 , 102 , 131 ], which will be detailed further in this review.…”
Section: Challenges and Solutionsmentioning
confidence: 99%
“…Ischemia and degeneration of follicles are important factors, which should be considered during the transplantation of ovarian tissue and it can cause a decline in ovarian reserve and fertility potential (5)(6)(7)(8). The vascular condition of the graft site plays a critical role in the reduction of ischemia.…”
Section: Introductionmentioning
confidence: 99%
“…The vascular condition of the graft site plays a critical role in the reduction of ischemia. Therefore, angiogenesis in transplanted tissue and growth of the ovarian follicles depends on the graft site (5,6,8). Vascular endothelial growth factor (VEGF) plays an important role in the posttransplantation angiogenesis of ovarian tissue (9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%